2020
DOI: 10.1108/pr-02-2020-0107
|View full text |Cite
|
Sign up to set email alerts
|

Spillover effects of organizational politics on family satisfaction: the role of work-to-family conflict and family support

Abstract: PurposeThis study considered organizational politics as a source of stress and examined its spillover effects on the family domain. By integrating the work–home resource theory and transactional theory of stress, the authors developed a moderated mediation model that examined the moderating role of family support in the relationship between employee's perceptions of organizational politics and their family satisfaction through work-to-family conflict.Design/methodology/approachThe authors examined the moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Social support has been found to be a resource that reduces the negative impact of occupational stress on workers’ health (Cohen and Syme, 1985 ; House, 1981 ) and of organizational politics (e.g., perceiving it is easier to remain quiet than to fight the system) and WIF on family satisfaction (Arefin et al, 2020 ). However, some have argued that for social support such as instrumental support to be beneficial, a person should receive a type of support that corresponds to their specific needs (French et al, 2018 ).…”
Section: Familial Factors Influencing Life Satisfactionmentioning
confidence: 99%
“…Social support has been found to be a resource that reduces the negative impact of occupational stress on workers’ health (Cohen and Syme, 1985 ; House, 1981 ) and of organizational politics (e.g., perceiving it is easier to remain quiet than to fight the system) and WIF on family satisfaction (Arefin et al, 2020 ). However, some have argued that for social support such as instrumental support to be beneficial, a person should receive a type of support that corresponds to their specific needs (French et al, 2018 ).…”
Section: Familial Factors Influencing Life Satisfactionmentioning
confidence: 99%
“…Perceived organisational politics is generally associated with increased psychological strain, burnout, turnover intentions and counterproductive work behaviours and low job satisfaction, organisational commitment, organisational trust, organisational justice and organisational citizenship behaviours (Chang et al , 2009). Moreover, organisational politics adversely affects organisational creativity (Xu et al , 2020) and employees' family satisfaction (Arefin et al , 2020b). Bergeron and Thompson (2020) found that perceived organisational politics negatively influences psychological uncertainty and employees' voice in the workplace.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, the studies in question investigated the role of WFC in other settings and among different samples (Rahman et al, 2019;Wu et al, 2016). Additionally, studies on WFC, particularly in the hospital setting, are limited, since most have been conducted in other settings such as the university and hospitality contexts (Arefin et al, 2020;O'Neill and Follmer, 2020). To achieve a deeper understanding of this relationship, we developed a model that tests the association between WFC and SWB in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%